Penerapan Sistem Pemupukan Biopori-Sludge Untuk Gerakan Ecofarming Pada Petani Di Desa Bayu Kecamatan Songgon Banyuwangi - M. Jiddan Farhan Fuady; Ika Yuniwati; Doni Aprilio; Aldy Bahaduri Indraloka; I Gusti Ngurah Agung Satriya Prasetya Dharma Yudha (PaKMas: Jurnal Pengabdian Kepada Masyarakat, 2022)
Coffee is one of the easily found commodities, especially in Indonesia. In tropical climates, coffee is easy to grow and thrive. Coffee is very easy to grow in the highlands. The need for coffee is increasing with large consumer demand. One of the villages in Banyuwangi that grow coffee is Bayu Village Songgon Subdistrict. Coffee farmers do planting, watering, fertilizing, and manually produce pests in Bayu Village. According to the survey’s findings, the fertilization process affects the coffee fruit produced on Bayu village plantations. Innovations in the Biopori-Sludge fertilization system were carried out based on these problems. This system uses infiltration holes as a way of fertilizer and water so that they can be absorbed properly by the roots. Fertilizers are used in the form of organic fertilizers derived from livestock waste belonging to residents. Biopori pit making uses a soil drilling machine designed to make it easier for farmers. The sleek design of this machine facilitates its portability from one location to another. The existence of this machine and system can help the process of planting and fertilizing coffee in Bayu Village. The existence of this activity has an impact on the implementation of sustainable eco-farming so that coffee cultivation carried out in Bayu Village is more environmentally friendly and economical.